Ultra-Processed Food Intake, Cumulative Antibiotic Exposure, and Markers of Gut Inflammation as Risk Factors for Early-Onset Colorectal Cancer:A Matched Case-Control Study in a Resource-Limited Community-Academic Health System - Basit Ur Rehman; Fareed Ullah; Ahmed Shahbaz; Jawad Ahmed (Pakistan Journal of Gastroenterology, 2026)
Background: Early-onset colorectal cancer (EOCRC), diagnosed in adults younger than 50 years, has increased at approximately 1.5–2.0% per year in both high-income and South Asian populations. The independent and joint roles of ultra-processed food (UPF) consumption, cumulative antibiotic exposure, and systemic inflammation have not been examined in resource-limited settings. Methods: We conducted a retrospective 1:2 matched case-control study at the Bolan Medical Complex / Sandeman Provincial Hospital, Quetta (2018–2026). Cases (n=174) were adults aged 18–49 with histologically confirmed colorectal adenocarcinoma (ICD-10 C18–C20); controls (n=348) were matched on age (±2 years), sex, race/ethnicity, BMI category, and index year. UPF intake was measured via a validated 28-item NOVA-adapted food frequency questionnaire. Antibiotic exposure was extracted from the pharmacy database. Inflammation markers (hsCRP, ESR, fecal calprotectin) were retrieved from the electronic health record. Conditional logistic regression estimated adjusted odds ratios. Mediation analysis quantified the proportion of the UPF–EOCRC association mediated by hsCRP elevation. STROBE guidelines were followed. Results: High UPF intake (top tertile, ≥9.8 servings/day) was independently associated with 65% higher odds of EOCRC (aOR 1.65; 95% CI 1.21–2.26). Cumulative antibiotic exposure ≥3 courses was associated with aOR 1.47 (95% CI 1.09–1.99). A statistically significant multiplicative interaction was observed between high UPF and ≥3 antibiotic courses (combined aOR 2.98; interaction OR 1.89; p=0.031). Elevated hsCRP mediated 24.3% (95% CI 12.1–38.6%) of the UPF–EOCRC association. Associations were stronger for distal/rectal tumours (aOR 1.82) than proximal tumours (aOR 1.31; p-heterogeneity=0.042) and amplified in the lowest SES quartile (aOR 2.04). Conclusions: High UPF intake and cumulative antibiotic exposure independently and synergistically increase odds of EOCRC, with a substantial proportion mediated through systemic inflammation. These findings identify actionable targets for dietary counselling, antibiotic stewardship, and risk-stratified screening in young South Asian adults.